Transformerless DC traction power conversion system design for light-rail-transit (LRT) - Chua T.Z.Y.; Ong Y.T.; Toh C.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
DC-DC converters; Electric rectifiers; Energy conversion; Low pass filters; MATLAB; Rectifying circuits; Urban transportation; Buck converters; Controlled rectifier; Conventional design; Light rail transit (LRT); Power conversion systems; Power electronics converters; Rectifier transformers; Traction power; Light rail transit